Prva iskustva sa primjenom ciljane i imunoterapije u liječenju melanoma : iskustvo jednog centra - Berendika, Jelena; Jungić, Saša; Tubić, Biljana; Rakita, Ivanka; Vještica, Milka; Đokanović, Dejan; Mirčeta, Nikolina; Gojković, Zdenka; Petković, Sanja; Marković Peković, Vanda (Scripta Medica, 2022)
Background / Aim: Up until ten years ago stage four melanoma was considered a disease with extremely poor prognosis. Standard therapy during this period of time was dacarbazine chemotherapy. Patients with better performance status were treated with immunotherapy cytokine IL-2. In the last ten years eight medications have been approved by the FDA for the therapy of melanoma. The goal of this study was to determine objective response rate (ORR), median overall survival (OS), median progression free survival (PFS) and safety in patients with advanced and metastatic cutaneous melanoma treated with targeted therapy and immunotherapy at the University Clinical Centre of the Republic of Srpska (Centre). Methods: A non-randomised observational retrospective/prospective trial was conducted to investigate first experiences with the use of targeted therapy and immunotherapy at the Centre and compare the results with the literature data. A total of 23 patients received BRAF targeted therapy for the treatment of metastatic cutaneous melanoma in the first line of treatment. Nine patients received vemurafenib, fourteen patients received a combination of BRAF/MEK inhibitor. Nine patients were treated with pembrolizumab immunotherapy. The trial was performed in a period from May 2017 until December 2020. Results: In patients receiving vemurafenib ORR was 44.4 %, median PFS was 5 months (95 % CI, 1 to 11) and the median OS was 9 months (95 % CI, 2 to 17). In the vemurafenib/cobimetinib group ORR was 71.4 %. Median PFS was 9 months and median OS was 12 months. ORR in patients receiving pembrolizumab was 22.9 %, median PFS was 3 months (95 % CI, 1 to 11) and the median OS was 4.5 months (95 % CI, 2 to 12). Results in all three groups were inferior compared to the results from the literature except for ORR in patients receiving vemurafenib and vemurafenib/cobimetinib. Adverse events were tolerable and manageable and were similar to those described in the literature. Conclusion: Based on the experience with the targeted and immunotherapy in the Centre, which was presented in this study, it was concluded that in conditions when there is limited access to drugs, the greatest benefit have the patients who meet the inclusion criteria in clinical trials.